2017
DOI: 10.3847/1538-4357/aa8095
|View full text |Cite
|
Sign up to set email alerts
|

Successive Two-sided Loop Jets Caused by Magnetic Reconnection between Two Adjacent Filamentary Threads

Abstract: We present observational analysis of two successive two-sided loop jets observed by the ground-based New Vacuum Solar Telescope (NVST) and the space-borne Solar Dynamics Observatory (SDO). The two successive two-sided loop jets manifested similar evolution process and both were associated with the interaction of two small-scale adjacent filamentary threads, magnetic emerging and cancellation processes at the jet's source region. High temporal and high spatial resolution observations reveal that the two adjacen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 73 publications
0
37
1
Order By: Relevance
“…Up to date, there are only a few observational example of two-sided-loop jets (Alexander & Fletcher 1999;Jiang et al 2013;Tian et al 2017). The two-sided-loop jets in Tian et al 2017 were suggested to be caused by magnetic reconnection between adjacent filamentary threads, which is not accordant with the model of Yokoyama & Shibata (1995.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Up to date, there are only a few observational example of two-sided-loop jets (Alexander & Fletcher 1999;Jiang et al 2013;Tian et al 2017). The two-sided-loop jets in Tian et al 2017 were suggested to be caused by magnetic reconnection between adjacent filamentary threads, which is not accordant with the model of Yokoyama & Shibata (1995.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…So far, the finding of blowout jets has been confirmed by many observational studies, and now we recognize that the vast majority of solar jets are caused by magnetic flux cancellation rather than flux emergence [63,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Recently, high-resolution observational studies have shown that two-sided-loop jets are also associated with flux cancellations and include the eruption of mini-filaments inside the base arches [44,46,49,85,86], and two-sidedloop jets occurring in filament channels may be important for causing the eruption of large filaments [87].…”
Section: Observational Feature (A) Morphology and Classificationmentioning
confidence: 99%
“…An anemone jet exhibits an inverted-Y shape consisting of a straight plasma beam and a bright dome-like base. By contrast, a two-sided-loop jet appears as a pair of plasma beams ejecting in opposite directions from the eruption source region [44][45][46][47][48][49]. Recently, high-resolution observations combined with extrapolated three-dimensional (3D) coronal magnetic fields revealed the fan-spine topology magnetic system of straight anemone jets [50], which consists of a coronal nullpoint, a dome-like fan that represents the [51][52][53][54][55][56][57][58][59][60].…”
Section: Observational Feature (A) Morphology and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconnection between MF1 and MF2 can be evidenced by several features: the sudden appearance of a small bright loop between G1 and G2 (see the red curve in Figure 1 (h)), the bi-directional plasma flows from the crossing site of the two MFs (see the two black arrows in Figure 1 (h)), and the formation of F1 as indicated by the black arrow in Figure 1 (i). Such kind of magnetic reconnection between two filaments were ob-served in several previous events, which was thought to be important for the generation of two-sided-loop solar jets and the formation of filaments (e.g., Tian et al 2017;Yang et al 2016;Xue et al 2017;Zheng et al 2017;Yang et al 2019;Chen et al 2016Chen et al , 2018. Another interesting feature during the eruption is the appearance and kinking eruption of a bright loop as indicated by the dotted blue curve (labeled with "loop") in Figure 1 (h) and (i).…”
Section: Resultsmentioning
confidence: 66%